PARKINSON'S DISEASE 'GET IT ON TIME' AUDIT. (29th November 2012) - Cameron Smail, R; McColgan, P; Pearce, R
Abstract : Introduction: In 2006 the charity Parkinson's UK launched the 'Get it on Time' campaign, to ensure that Parkinson's disease patients were given their appropriate medications whilst in hospital in a timely manner. We set out to audit the prescription and administration of PD meds in a 6 month period. Objectives: To identify delays or omissions in the prescription and administration of PD medicines, and identify the prescription of contraindicated medicines. Methods: A sample of inpatient episodes for PD patients were taken for the period 1 February to 1 August 2011 in one south east England DGH. Omissions and delays of medications, and the related reasons were recorded in accordance with Parkinson's UK audit guidelines. Results: 48 patient episodes for 44 patients (17 female, 27 male) were audited. The average patient age was 77, and average length of stay was 15 days. 21 patients (43%) experienced a delay in their first dose whilst in hospital. 12 patients (25%) experienced further delays. 156 omitted doses were identified, equivalent to one dose missed for every five patient-days in hospital. 25% of these omissions were deemed to be unjustified or unexplained. Conclusions: This audit demonstrated significant shortcomings in the administration of medications, both at the time of admission, and throughout the inpatient stay. A large proportion of omissions were for correctible causes such as the drugs not being available. Further doctor, nurse and pharmacist education will be carried out to ameliorate the problem, and a further audit cycle is to be undertaken.